Cristina Viñuela. 2004. Victoria Ocampo. De la búsqueda al conflicto, prólogo por Pedro L. Barcia. Mendoza: Universidad Nacional de Cuyo, 269 p. - Avenatti de Palumbo, Cecilia Inés (2006)
Fil: Avenatti de Palumbo, Cecilia Inés. Pontificia Universidad Católica Argentina